Placenta Previa with History of Previous Caesarean Delivery – an Obstetrician's Nightmare - Mazumder, U; Rouf, S; Sarkar, S (Journal of Women's Reproductive Health, 2017)
Background: The nature of placenta previa can be unpredictable and harsh on the mother and baby. These complications are often unpredictable, unpreventable and often leave the labour ward team in a dilemma. This Obstetricians' nightmare is fortunately a rare complication. The frequency of placenta previa at the time of delivery average 1/200 births i.e. 0.5%. Placenta previa is still an important cause of maternal and fetal death in our country. The risk factors are Advanced Maternal age, Multi parity, Previous Cesarean Section, Multiple gestation, Previous Abortions, Previous intrauterine surgery, placenta previa in previous pregnancy, Smoking. Objective: Identification of risk factors, the feto-maternal outcome and complications of patients having placenta previa with previous caesarean section. Methodology: This cross sectional study was conducted from July 2012 to June 2015 in Obstetrics and Gynaecology department, Dhaka Medical College hospital. 100 patients of placenta previa were included in this study. Non-probability purposive sampling method was used for selection of patients. Results: In this study, Socio-demographic profiles, Identification of risk factors, the feto-maternal outcome and complications of patients having placenta previa were assessed. The frequency of placenta previa associated with previous cesarean section was 61%. In demographic profiles of the patients in this study - with a history of previous caesarean section, 78.7% patients were in the age group 26-35. Multiparity was predominant on scarred uterus group (63.9%). Here, demonstrated that > 2 previous history of caesarean section was associated with 80.3% of placenta previa. Regarding maternal outcome, complications like massive haemorrhage, ureteral injury, bladder injury, wound infection, DIC, maternal and perinatal mortality were more in the scarred patients than in the unscarred patients. In our study, 29.5% of morbid adhesion of placenta observed in scarred uterus. Conclusions: There is significant association of placenta previa with previous cesarean delivery. So, Careful monitoring of high risk pregnancies is of utmost importance. Avoidance of unnecessary caesarean sections and early week’s pregnancy terminations can minimize the Obstetricians' nightmare.
Keywords: Placenta previa; Postpartum haemorrhage; maternal outcome; Scarred and uuscarred uteru; Caesarean section; Obstetricians' nightmare